Perception of Farmers Concerning the Impact of Panyaweuyan Terrace Tourism in Majalengka, Indonesia - Sudrajat, Sudrajat (Faculty of Geography, Universitas Gadjah Mada, 2025)
The increase in tourist visits to Panyaweuyan terrace is observed to have a positive impact. However, negative effects are being felt by farmers in the surrounding areas of the tourist site. Therefore, this research aimed to examine the socio-economic characteristics of farmers and perception concerning impact of Panyaweuyan terrace tourism activities on the socio-cultural, economic, and environmental aspects. The basic method of this research was a survey, including a sample of farmers for interviews. Additionally, primary data were collected through in-depth interviews with several informants. The Likert scale data analysis was performed using quartile (Q) method and analyzed descriptively and qualitatively. The results of the research showed that the socio-economic conditions of farmers around Panyaweuyan terrace tourism area were quite diverse. According to perception of farmers, tourism activities in the area had a positive impact on both the socio-cultural and economic aspects of community. However, farmers still perceived negative impact on the socio-cultural and environmental aspects. Based on these results, management should be community-based and sustainable to minimize the negative impact of Panyaweuyan terrace tourism.Received: 2024-08-04 Revised: 2024-08-20 Accepted: 2025-04-11 Published: 2025-04-28